2021
DOI: 10.3389/fagro.2021.630596
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Biostimulants on Induced Plant Defense

Abstract: The search for innovative and alternative methods for chemical control to manage pests is an increasingly growing reality. The use of biostimulants such as plant growth promoting rhizobacteria (PGPR) and humic acids (HA) has been shown to improve many agronomic characteristics of plants while increasing yield. These biostimulants also alter the production of secondary metabolites with consequences for insect herbivores. Here we review the role of biostimulants such as PGPR and HA in promoting and eliciting pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 92 publications
(106 reference statements)
1
18
0
Order By: Relevance
“…The individual use of these biostimulants in biocontrol has already been established in the literature; however, there have been few reports on the mechanisms involved in the interaction of these biostimulants on the protection of plants against pathogens (Glick, 2015;Jindo et al, 2020;Pereira et al, 2021). We hypothesize that HSs and PGPB can use different approaches to contribute to the plant's defense mechanisms, such as (1) combined application of these biostimulants is capable of altering secondary plant metabolism and pathways related to stress responses, providing the plant with greater tolerance to biotic stress.…”
Section: Humic Substances and Plant Growth-promoting Bacteria In Biocontrolmentioning
confidence: 99%
See 2 more Smart Citations
“…The individual use of these biostimulants in biocontrol has already been established in the literature; however, there have been few reports on the mechanisms involved in the interaction of these biostimulants on the protection of plants against pathogens (Glick, 2015;Jindo et al, 2020;Pereira et al, 2021). We hypothesize that HSs and PGPB can use different approaches to contribute to the plant's defense mechanisms, such as (1) combined application of these biostimulants is capable of altering secondary plant metabolism and pathways related to stress responses, providing the plant with greater tolerance to biotic stress.…”
Section: Humic Substances and Plant Growth-promoting Bacteria In Biocontrolmentioning
confidence: 99%
“…These microorganisms also play a relevant role in biological control. PGPB induce biochemical and plant defense responses, causing induced systemic resistance (ISR; Pereira et al, 2021). In addition to synthesizing compounds that inhibit the growth of pathogens, they can also induce greater production of allelochemicals and change the composition of exudates in plants, contributing to a reduction in pest development (Bashan et al, 2014;Pankievicz et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indirectly, the effect of HS can be associated with the effects of other organic matter sources, such as V, C and teas in the control of pests and diseases in plants, since HS are ubiquitous in all natural organic material. HS can indirectly induce the plant's defense system against harmful microorganisms by inhibition mechanisms or by promoting the growth of microorganisms antagonists of pathogens, thus allowing greater protection for plants [88]. We found in the literature one evidence highlighting the relationship between plant defense mechanism and HS.…”
Section: Main Organic Matter Sources Used In Plant Pest and Disease C...mentioning
confidence: 71%
“…De Hita et al [131] reported the increase of SA and JA in cucumber plants, 24 and 72 h after HA foliar application, respectively, indicating a possible effect on the activation of SA and JA signaling pathways as plant defense response. Based on the evidence found in literature, humified organic matter may be involved with RAS [17,88,119,120,131], but further studies are needed to prove it.…”
Section: Mechanisms Of Bio-based Pest and Disease Inhibitionmentioning
confidence: 99%